1–forms (translations)#

by Stéphane Haussler

Translations#

A generic translation in spacetime is expressed with a 4-vector:

\[\begin{split}T^♯ = \left[ \begin{alignedat}{1} A^t & ∂_t \\ A^x & ∂_x \\ A^y & ∂_y \\ A^z & ∂_z \\ \end{alignedat} \right]\end{split}\]

Flattened, the translation expressed in differential form is:

\[\begin{split}T^♭ = \left[ \begin{alignedat}{2} & A^t & dt \\ - & A^x & dx \\ - & A^y & dy \\ - & A^z & dz \\ \end{alignedat} \right]\end{split}\]

\(⋆ T^♭\)#

\[\begin{split}⋆ T^♭ = \left[ \begin{alignedat}{2} & A^t & dx ∧ dy ∧ dz \\ - & A^x & dt ∧ dy ∧ dz \\ - & A^y & dt ∧ dz ∧ dx \\ - & A^z & dt ∧ dx ∧ dy \\ \end{alignedat} \right]\end{split}\]

\(d T^♭\)#

\[\begin{split}d T^♭ = \left[ \begin{alignedat}{1} ( & - & ∂_t A^x & - & ∂_x A^t) & \; dt ∧ dx \\ ( & - & ∂_t A^y & - & ∂_y A^t) & \; dt ∧ dy \\ ( & - & ∂_t A^z & - & ∂_z A^t) & \; dt ∧ dz \\ ( & - & ∂_y A^z & + & ∂_z A^y) & \; dy ∧ dz \\ ( & - & ∂_z A^x & + & ∂_x A^z) & \; dz ∧ dx \\ ( & - & ∂_x A^y & + & ∂_y A^x) & \; dx ∧ dy \\ \end{alignedat} \right]\end{split}\]

\(d⋆ T^♭\)#

\[d ⋆ T^♭ = \left( ∂_t A^t + ∂_x A^x + ∂_y A^y + ∂_z A^z \right) \; dt ∧ dx ∧ dy ∧ dz\]

\(⋆d T^♭\)#

\[\begin{split}⋆ d T^♭ = \left[ \begin{alignedat}{4} (+ & ∂_z A^y & - & ∂_y A^z & ) & \; dt ∧ dx \\ (+ & ∂_x A^z & - & ∂_z A^x & ) & \; dt ∧ dy \\ (+ & ∂_y A^x & - & ∂_x A^y & ) & \; dt ∧ dz \\ (+ & ∂_x A^t & + & ∂_t A^x & ) & \; dy ∧ dz \\ (+ & ∂_y A^t & + & ∂_t A^y & ) & \; dz ∧ dx \\ (+ & ∂_z A^t & + & ∂_t A^z & ) & \; dx ∧ dy \\ \end{alignedat} \right]\end{split}\]

\(⋆d⋆ T^♭\)#

\[⋆d⋆ T^♭ = ∂_t A^t + ∂_x A^x + ∂_y A^y + ∂_z A^z\]

\(d⋆d T^♭\)#

\[\begin{split}d⋆d T^♭ = \left[ \begin{alignedat}{7} ( & + ∂_x^2 A^t & + ∂_y^2 A^t & + ∂_z^2 A^t & + ∂_t ∂_x A^x & + ∂_t ∂_y A^y & + ∂_t ∂_z A^z & ) \; dx ∧ dx ∧ dy \\ ( & + ∂_t^2 A^x & - ∂_y^2 A^x & - ∂_z^2 A^x & + ∂_t ∂_x A^t & + ∂_x ∂_y A^y & + ∂_z ∂_x A^z & ) \; dt ∧ dy ∧ dz \\ ( & + ∂_t^2 A^y & - ∂_x^2 A^y & - ∂_z^2 A^y & + ∂_t ∂_y A^t & + ∂_y ∂_z A^z & + ∂_x ∂_y A^x & ) \; dt ∧ dz ∧ dx \\ ( & + ∂_t^2 A^z & - ∂_x^2 A^z & - ∂_y^2 A^z & + ∂_t ∂_z A^t & + ∂_z ∂_x A^x & + ∂_y ∂_z A^y & ) \; dt ∧ dx ∧ dy \\ \end{alignedat} \right]\end{split}\]

\(d⋆d⋆ T^♭\)#

\[\begin{split} d⋆d⋆ T^♭ = \left[ \begin{alignedat}{7} ( & ∂_t ∂_x A^x & \: + \: & ∂_t ∂_y A^y & \: + \: & ∂_t ∂_z A^z & ) & \; dt \\ ( & ∂_t ∂_x A^t & \: + \: & ∂_x ∂_y A^y & \: + \: & ∂_z ∂_x A^z & ) & \; dx \\ ( & ∂_t ∂_y A^t & \: + \: & ∂_y ∂_z A^z & \: + \: & ∂_x ∂_y A^x & ) & \; dy \\ ( & ∂_t ∂_z A^t & \: + \: & ∂_z ∂_x A^x & \: + \: & ∂_y ∂_z A^y & ) & \; dz \\ \end{alignedat} \right]\end{split}\]

\(⋆d⋆d T^♭\)#

\[\begin{split}⋆d⋆d T^♭ = \left[ \begin{alignedat}{7} ( & + ∂_x^2 A^t & + ∂_y^2 A^t & + ∂_z^2 A^t & + ∂_t ∂_x A^x & + ∂_t ∂_y A^y & + ∂_t ∂_z A^z & ) \; dt \\ ( & + ∂_t^2 A^x & - ∂_y^2 A^x & - ∂_z^2 A^x & + ∂_t ∂_x A^t & + ∂_x ∂_y A^y & + ∂_z ∂_x A^z & ) \; dx \\ ( & + ∂_t^2 A^y & - ∂_x^2 A^y & - ∂_z^2 A^y & + ∂_t ∂_y A^t & + ∂_y ∂_z A^z & + ∂_x ∂_y A^x & ) \; dy \\ ( & + ∂_t^2 A^z & - ∂_x^2 A^z & - ∂_y^2 A^z & + ∂_t ∂_z A^t & + ∂_z ∂_x A^x & + ∂_y ∂_z A^y & ) \; dz \\ \end{alignedat} \right]\end{split}\]

\((⋆d⋆d - d⋆d⋆) T^♭\)#

\[\begin{split}(⋆ d ⋆ d - d ⋆ d ⋆) T^♭ = \left[ \begin{alignedat}{7} ( & & + ∂_x^2 A^t & + ∂_y^2 A^t & + ∂_z^2 A^t & ) \; dt \\ ( & + ∂_t^2 A^x & & - ∂_y^2 A^x & - ∂_z^2 A^x & ) \; dx \\ ( & + ∂_t^2 A^y & - ∂_x^2 A^y & & - ∂_z^2 A^y & ) \; dy \\ ( & + ∂_t^2 A^z & - ∂_x^2 A^z & - ∂_y^2 A^z & & ) \; dz \\ \end{alignedat} \right]\end{split}\]